2019
DOI: 10.1039/c8ra09305a
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the phyto-interaction of heavy metal oxide bulk and nanoparticles: evaluation of seed germination, growth, bioaccumulation, and metallothionein production

Abstract: Phyto-interaction of heavy metal oxide nano and bulk particles with agriculturally important crops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…However, in the current scenario industrial waste is the leading cause of soil pollution [ 2 ]. Heavy metals (Cr, Hg, Cd, As, Co) cannot be degraded into harmless form and they transfer in the food chain, and their bio-magnification causes toxicity and disturbs the ecosystem [ 3 , 4 , 5 ]. Chromium (Cr) is one of the toxic heavy metals present in industrial effluents.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the current scenario industrial waste is the leading cause of soil pollution [ 2 ]. Heavy metals (Cr, Hg, Cd, As, Co) cannot be degraded into harmless form and they transfer in the food chain, and their bio-magnification causes toxicity and disturbs the ecosystem [ 3 , 4 , 5 ]. Chromium (Cr) is one of the toxic heavy metals present in industrial effluents.…”
Section: Introductionmentioning
confidence: 99%
“…Studies dealing with the effects of NMs establish that many factors can have an impact on the exact outcome of the NM–plant interactions, including the plant species, the size of the applied NMs, the duration or existence of pre-cultivation (e.g., seed priming), the concentration and span of NM exposure or the growing conditions, namely the germination test performed in Petri dishes or hydroponics or a pot experiment using soil. To date, it has been well documented by reviews and case studies that how several NMs, mainly metallic NPs, may positively or negatively influence biomass, the photosynthetic activity or the yield of adult plants, but there remains a great lack of knowledge concerning the early developmental stage, i.e., seed germination and early seedling growth [ 27 , 28 , 29 ]. The uptake of NMs by mature (adult) plants has been documented by several studies.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it is found that Zn NP treated wheat seeds surpassed elemental Zn values over ZnSO 4 , indicating that NPs are more e cient at delivering Zn to plant tissues than ZnSO 4 , which suggests it is done during a particle-speci c mechanism (Baddar et al 2018). Similar studies have shown that accumulation of Zn from NP treatment was more than predicted values upon dissolved Zn concentration (Ahmed et al 2019). However, Zn is an essential metal for plant growth, it may be a phytotoxic metal when exceeds the tolerance limit depending on the plant species or plant's studied part (Zaeem et al 2020).…”
Section: Discussionmentioning
confidence: 89%